Primary periphyseal stress injuries in young athletes: a systematic review - Caine, D.; Meyers, R.; Nguyen, J.; Schöffl, V.; Maffulli, N. (Sports Medicine, 2022)
Background: Overuse injuries are common in sporting children and adolescents. These injuries are a particular concern when they involve the epiphyseal-physeal-metaphyseal (EPM) complex given their potential to disturb skeletal growth. Specifically, the limits of mechanical tolerance of the EPM complex to repetitive stress may be exceeded by the intense and continuous training characteristic of many youth sports today. Objective: This article describes the present status of knowledge on the occurrence and outcome of primary periphyseal stress injuries (PPSIs) affecting the EPM complex in the extremities of children and adolescents involved in youth sports. Methods: A comprehensive review of the sports medicine literature was conducted to determine the nature and extent of PPSIs affecting the EPM complex of the extremities among youth sports participants and the potential for consequent skeletal growth disturbance and resultant limb deformity associated with these injuries. Results: Our initial search uncovered 128 original published scientific articles reporting relevant data on PPSIs. There were 101 case reports/series, 19 cross-sectional, 1 case-control, and 7 cohort studies with relevant data. The case reports/series studies reported 448 patients with PPSIs involving the extremities. Children and adolescents representing a variety of high impact repetitive youth sports activities—including baseball, badminton, climbing, cricket, dance, gymnastics, rugby, soccer, swimming, tennis, and volleyball—may sustain PPSIs involving the shoulder, elbow, hand and wrist, knee, and ankle and foot. Although incidence data from prospective cohort studies are lacking, data arising from cross-sectional studies suggest that PPSIs may be common in select groups of youth athletes—including the shoulder in baseball players (0-36.6%), wrist in gymnasts (10-83%) and platform divers (52.6%), and fingers in rock climbers (5-58%). Notably, not all stress-related skeletal changes detected on imaging were symptomatic in these studies. When diagnosed and treated with an appropriate period of rest and rehabilitation, most patients studied were able to return to their sport activities. However, our data also show that 57/448 PPSIs (12.7%) produced growth disturbance, and that 28/448 patients (6.2%) underwent surgery for their injuries. Absence of treatment, delayed presentation and diagnosis, and non-compliance with a rest regimen were common in cases that produced growth disturbance. Conclusions: PPSIs may affect the extremities of children and adolescents engaged in a variety of youth sports, especially at advanced levels of training and competition. Most skeletally immature patients with PPSIs respond well to timely treatment; however, in extreme cases, PPSIs can progress to produce skeletal growth disruption which may necessitate surgical intervention. Clearly, establishing the early diagnosis of PPSIs and providing timely treatment of these injuries are needed to ensure the skeletal health of youth sports participants. Rigorous prospective longitudinal epidemiological and imaging studies designed to provide incidence rates of PPSIs and to determine the effect of PPSIs on long-term skeletal health are also necessary.